Eclipse-induced geomagnetic signatures: the 2024 EZIE-Mag citizen science campaign contribution to the Heliophysics Big Year - Mesquita, Rafael L. A.; Barnes, Robin; Gjerloev, Jesper; Eisape, Adebayo; Mosavi, Nelli; Eidson, Robert (Frontiers in Astronomy and Space Sciences, 2025)
The 8 April 2024, total solar eclipse presented a unique opportunity to study ionospheric and magnetospheric responses to local changes in the solar illumination. As part of NASA’s citizen science initiative, we launched the EZIE-Mag Eclipse Measurement Campaign and deployed ultra low-cost, science-grade magnetometer kits operated by trained citizen scientists across diverse geographic locations. This grassroots decentralized approach enabled the collection of high-quality, distributed geomagnetic data. Observations from Muncie, Indiana, revealed a clear signal that is interpreted as being produced by eclipse-induced current system perturbations. This is an excellent example of complex electrodynamic coupling between the Sun and the magnetosphere-ionosphere-atmosphere environment. The results not only contribute to advancing Heliophysics research but also demonstrate the value of citizen science in enhancing space weather awareness and public education. The campaign’s inclusive approach in engaging participants from various backgrounds, underscores the potential for scalable, community-driven efforts to broaden participation and deepen public understanding of space weather phenomena.